2004
DOI: 10.1161/01.cir.0000129312.43547.08
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Binding of Activated Factor VII Triggers Smooth Muscle Cell Proliferation via Extracellular Signal–Regulated Kinase Activation

Abstract: Background-Tissue factor (TF) is the main initiator of coagulation in vivo. Recently, however, a role for TF as a cell receptor involved in signal transduction has been suggested. The aim of the present study was to assess whether activated factor VII (FVIIa) binding to TF could induce smooth muscle cell (SMC) proliferation and to clarify the possible intracellular mechanism(s) responsible for this proliferation. Methods and Results-Cell proliferation was induced by FVIIa in a dose-dependent manner, as assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 29 publications
2
65
0
Order By: Relevance
“…Indeed, FVIIa-initiated fibrin clot forma- tion is critical to control active bleeding immediately after wounding occurs and FXa, thrombin and fibrin have been shown to affect wound healing through a number of mechanisms, for example, as chemotactic and mitogenic factors for leukocytes (41)(42)(43). However, several considerations encouraged an exploration of other mechanisms to identify roles of FVIIa, independent of thrombin generation, in regulation of wound healing: (a) restoring thrombin generation in hemophilia B did not normalize wound healing to the level of WT mice (44); (b) the response of FVIIa treatment in keratinocytes is abrogated by TF-neutralizing antibody, but is not affected by hirudin (26); (c) FVIIa signaling, independent of coagulation, affects smooth muscle cell migration and proliferation (45), as well as transcriptional responses in keratinocytes (26); and (d) FVIIa-mediated inflammatory signaling, independent of thrombin and FXa, has been shown to occur in the response of mice to lethal endotoxemia (32). In addition, the initial observations in this study, for example, the extended delay of wound healing up to day 11 post wound, the reduced keratinocyte migration, and the diminished inflammation in FVII tTA/tTA mice, suggest that the role of FVII in wound healing extends beyond the coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, FVIIa-initiated fibrin clot forma- tion is critical to control active bleeding immediately after wounding occurs and FXa, thrombin and fibrin have been shown to affect wound healing through a number of mechanisms, for example, as chemotactic and mitogenic factors for leukocytes (41)(42)(43). However, several considerations encouraged an exploration of other mechanisms to identify roles of FVIIa, independent of thrombin generation, in regulation of wound healing: (a) restoring thrombin generation in hemophilia B did not normalize wound healing to the level of WT mice (44); (b) the response of FVIIa treatment in keratinocytes is abrogated by TF-neutralizing antibody, but is not affected by hirudin (26); (c) FVIIa signaling, independent of coagulation, affects smooth muscle cell migration and proliferation (45), as well as transcriptional responses in keratinocytes (26); and (d) FVIIa-mediated inflammatory signaling, independent of thrombin and FXa, has been shown to occur in the response of mice to lethal endotoxemia (32). In addition, the initial observations in this study, for example, the extended delay of wound healing up to day 11 post wound, the reduced keratinocyte migration, and the diminished inflammation in FVII tTA/tTA mice, suggest that the role of FVII in wound healing extends beyond the coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although evaluation in silico in another study did not indicate effects of the 4 investigated polymorphisms on transcription factor binding [11], gel shift experiments by Terry et al indeed demonstrated such effects of the Del-1208Ins polymorphism, providing a possible explanation for the genotypic differences in TF expression and activity [17]. An influence on local TF activity in the vessel wall may in turn modulate processes involved in atherosclerosis such as inflammation and VSMC migration and proliferation [2,9,10,[25][26][27][28][29][30], which could result in measurable differences in C-IMT as observed in this study. We cannot rule out, however, that the observed effect of A/G TF promoter haplotype on C-IMT may be explained by linkage disequilibrium with other genetic variants influencing the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, experimental studies in vitro and in vivo have shown involvement of TF in inflammation and VSMC migration/proliferation mediated via intracellular signalling by the TF cytoplasmic tail and/or TF:FVIIa-promoted extracellular proteolytic cascades and activation of protease-activated receptors (PARs) [2,9,10,[25][26][27][28][29][30]. The association between tertiles of TF and C-IMT, tested by multivariable linear regression analysis, was analysed in the subgroup of subjects (n = 120) who underwent plasma TF level determinations.…”
Section: Discussionmentioning
confidence: 99%
“…Factor VII activation by tissue factor initiates the enzymatic interaction and determines its magnitude and location [208,209,212]. Factors IX and X amplify Factor VII thrombin production to moderate levels that energize tissue repair [27,121,215].…”
Section: The Tissue Repair Component Inflammation and Apoptosismentioning
confidence: 99%